Pendekatan Falsafah Dalam Perbincangan 'Ilm Al-Kalam Menurut Al-Mutakallimun - Hamat, Mohd Fauzi (Jurnal Usuluddin, 1998)
This article tries to elaborate the use of philosophical approach among the former Islamic thinkers like al-Muktazilah and al-Asya'irah in their discussion of Islamic thought especially in Theology. The sort of this tendency which totally contradict to the Qur'anic approach contributes in making this discipline not easier to be understood by the Muslims especially common people.